(untitled) (Applied Biological Research, 2017)
Rare-earth compounds are of immense significance due to the presence of f-orbital electrons and the resultant magnetic, electronic, catalytic, chemical and optical qualities. This leads to their practical application in diverse fields, such as luminescent devices or phosphors (component in LEDs, household compact fluorescent lamps, high-resolution flat panel displays), medical diagnostics and imaging, biochemical probes, powerful magnets, sensors, and in the catalysis of some technically important chemical processes. However, much attention has recently been devoted to the synthesis of rare-earth-based compounds in nanometric dimensions that can perform multiple functions, such as fluorescence imaging, drug delivery, and so on. In this mini review, a short summary of the applications of rare-earth nanomaterials in the fluorescent labelling of cells, MRI contrast imaging, and dual imaging modalities have been discussed.